Nitrite inhibition of microalgae induced by the competition between microalgae and nitrifying bacteria. (1st April 2020) - González-Camejo, J.; Montero, P.; Aparicio, S.; Ruano, M.V.; Borrás, L.; Seco, A.; Barat, R.
Abstract: Outdoor microalgae cultivation systems treating anaerobic membrane bioreactor (AnMBR) effluents usually present ammonium oxidising bacteria (AOB) competition with microalgae for ammonium uptake, which can cause nitrite accumulation. In literature, nitrite effects over microalgae have shown controversial results. The present study evaluates the nitrite inhibition role in a microalgae-nitrifying bacteria culture. For this purpose, pilot- and lab-scale assays were carried out. During the continuous outdoor operation of the membrane photobioreactor (MPBR) plant, biomass retention time (BRT) of 2 d favoured AOB activity, which caused nitrite accumulation. This nitrite was confirmed to inhibit microalgae performance. Specifically, continuous 5-d lab-scale assays showed a reduction in the nitrogen recovery efficiency by 32, 42 and 80% when nitrite concentration in the culture accounted for 5, 10 and 20 mg N·L −1, respectively. On the contrary, short 30-min exposure to nitrite showed no significant differences in the photosynthetic activity of microalgae under nitrite concentrations of 0, 5, 10 and 20 mg N·L −1 . On the other hand, when the MPBR plant was operated at 2.5-d BRT, the nitrite concentration was reduced to negligible values due to increasing activity of microalgae and nitrite oxidising bacteria (NOB). This allowed obtaining maximum MPBR performance; i.e. nitrogen recovery rate (NRR) and biomass productivity of 19.7 ± 3.3 mg N·L −1 ·d −1 and 139 ± 35 mg VSS·L −1 ·d −1, respectively; while nitrification rate (NOxR) reached the lowest value (13.5 ± 3.4 mg N·L −1 ·d −1 ). Long BRT of 4.5 d favoured NOB growth, avoiding nitrite inhibition. However, it implied a decrease in microalgae growth and the accumulation of nitrate in the MPBR effluent. Hence, it seems that optimum BRT has to be within the range 2–4.5 d in order to favour microalgae growth with respect to AOB and NOB. Graphical abstract: Image 1 Highlights: Nitrite concentrations of 5, 10 and 20 mg N·L −1 showed microalgae inhibition. BRT played a key role in the nitrite accumulation in the MPBR plant. Nitrite concentration reached values over 10 mg N·L −1 at 2-d BRT. 2.5-d BRT reduced nitrite due to increasing microalgae and NOB activity. 4.5-d BRT did not accumulate nitrite but increased nitrate concentration.